Strategic determinants of the formation of the migration policy of Ukraine - Borysenko , Olga (Theory and Practice of Public Administration, 2019)
The article deals with the problems that cause the activation of migration processes in Ukraine. Attention is drawn to the factor of wages of Ukrainians, which is the main reason why Ukrainians continue go abroad. The main threats to Ukraine are noted due to the growing emigration of Ukrainian citizens. Migration policy is closely linked to the country's socio-economic policy, foreign-policy processes in Ukraine and the world, migration policies of other countries. The difference in wages and quality of life was and remains the main reason why Ukrainians go abroad. Labor market imbalance causes migration, largely due to lack of system interaction between stakeholders: government, system vocational education, employees and employers. Solving this problem is a systemic and complex task, subordinated to goals and outcomes with other areas of public administration, based on pre-established and other policy-based frameworks. Can't be effective migration policy without effective economic, social, demographic, environmental and other components of the country's development.Migration policy should be built on the basis of identifying its strategic determinants, namely: formation of the strategy of the state migration policy of Ukraine on the basis of coordination of its goals and tasks with the goals and objectives of the related strategies incorporated into the overall strategy of sustainable development of Ukraine, observing the principles of consistency, integrity, complexity, subordination, succession; development of mechanisms of state regulation of migration processes, which make it possible to influence in a necessary way the causes migration and move to a model of migration policy based on protectionism national interests, liberalization of visa modes, lobbying on certain categories of citizens; formation of functions of control, monitoring and analysis of migration processes as an indicator of the effectiveness of the state regulation process; placing the emphasis of modern migration policy on the formation of regional conditions for the optimization of migration processes.